Design, synthesis, and biological evaluation of 3-chloro-2-oxo-N-(arylcarbamoyl)-2H-1-benzopyran-6-sulfonamide derivatives as potential DPP-IV inhibitors - Vawhal, Pallavi Kishor; Jadhav, Shailaja B. (International journal of health sciences, 2022)
In present work, we aimed at preparing coumarin and sulfonamide containing moieties into a single candidate template i.e. 3-chloro-2-oxo-N-(arylcarbamoyl)-2H-1-benzopyran-6-sulfonamides for the purpose of synergistic activity as potent DPP-IV inhibitors. The designed derivatives were subjected for the calculations of Lipinski rule, Veber’s rule, ADME analysis, drug-likeness properties and molecular docking. The derivatives which successfully passed all the criteria were proceeded for wet lab synthesis and biological evaluation. From the initial screening through Lipinski rule, Veber’s rule, ADME calculations, and drug-likeness properties, molecules 1a, 1f, 1g, 1h, 1i, 1j, 1k, 1o, 1p, 1q, 1r, 1v, 1w, and 1x successfully passed all the filters and displayed most drug-likeness nature. Therefore only these molecules were subjected for molecular docking studies. From molecular docking results, we have selected 1f, 1g, 1i, 1j, and 1v for the wet lab synthesis and biological evaluation. The structures of all the synthesized compounds were confirmed by spectral analysis and were subjected for in vitro DPP-IV enzyme assay. Sitagliptin was used as standard for the assay and it displayed 0.018 µM IC50 value. Compound 1f, 1g, 1i, 1j, and 1v exhibited 15.55, 15.85, 13.95, 14.48, and 13.45 µM IC50 values respectively.